Urinary stone detection and characterisation with dual-energy CT urography after furosemide intravenous injection: preliminary results. - Botsikas, Diomidis; Hansen, Catrina; Stefanelli, Salvatore; Becker, Christoph D; Montet, Xavier (European Radiology, 2014)
Objectives: To investigate the added advantage of IV furosemide injection and the subsequent urine dilution in the detection of urinary calculi in the excretory phase of dual-source dual-energy (DE) computed tomography (CT) urography, and to investigate the feasibility of characterising the calculi through diluted urine.Methods: Twenty-three urinary calculi were detected in 116 patients who underwent DECT urography for macroscopic haematuria with a split bolus two- or three-acquisition protocol, including a true unenhanced series and at least a mixed nephrographic excretory phase. Virtual unenhanced images were reconstructed from contrast-enhanced DE data. Calculi were recorded on all series and characterised based on their X-ray absorption characteristics at 100 kVp and 140 kVp in both true unenhanced and nephrographic excretory phase series.Results: All calculi with a diameter more than 2 mm were detected in the virtual unenhanced phase and in the nephrographic excretory phase. Thirteen of these calculi could be characterised in the true unenhanced phase and in the mixed nephrographic excretory phase. The results were strictly identical for both phases, six of them being recognised as non-uric acid calculi and seven as uric acid calculi.Conclusions: Mixed nephrographic excretory phase DECT after furosemide administration allows both detection and characterisation of clinically significant calculi, through the diluted urine.Key Points: • Urinary tract stones can be detected on excretory phase through diluted urine. • Urinary tract stone characterisation with dual-energy CT (DECT) is possible through diluted urine. • A dual energy split-bolus CT urography simultaneously enables urinary stone detection and characterisation.